Environmental & architectural phenomenology. Vol. 32, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2021)
Besides “Items of interest,” and “citations received,” this issue includes the following items: Zoologist Stephen Wood’s commentary relating to the phenomenology of animal welfare; Environmental psychologist Claudia Mausner discussion of liminality, place, home, and multiple “homes”; Architect Tim White’s firsthand examination of the human-sustaining walkability of Florence, Italy; Geographer Edward Relph’s overview of the future of places and place experiences in the 21st century; Architect Levent Şentürk’s effort to summarize graphically the work of urban designer Kevin Lynch’s seminal The Image of the City (1961).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals